Respuesta :

For this case we have the following equation:

[tex]2 (x + 2) = x-4[/tex]

Applying distributive property to the terms within the parentheses on the left side of the equation we have:

[tex]2x + 4 = x-4[/tex]

Subtracting "x" on both sides of the equation we have:

[tex]2x-x + 4 = -4\\x + 4 = -4[/tex]

Subtracting 4 on both sides of the equation we have:

[tex]x = -4-4\\x = -8[/tex]

Answer:

[tex]x = -8[/tex]

Answer:

x = -8

Step-by-step explanation:

We are given that Manuela solved following equation and we are to find its solution:

[tex] 2 ( x + 2 ) = x - 4 [/tex]

Expanding the left side of the equation by multiplying the terms inside the bracket by 2:

[tex]2x+4=x-4[/tex]

Arranging the equation in a way such that like terms are on each side (variables on the left and constants on the right):

[tex]2x-x=-4-4[/tex]

x = -8

ACCESS MORE